On the neutron contribution to the exposure level onboard space vehicles - Spurný, František; Ploc, Ondřej; Dachev, T (Radiation protection dosimetry, 2007)
The neutron contribution to the spacecraft crew exposure could represent an important part of the total dose equivalent value. The determination of this contribution represents a rather complex and difficult task, both through experimental and theoretical estimation. This paper will present an attempt to determine the neutron contribution onboard the International Space Station and Foton capsule using the data measured by means of a Si-diode based energy deposition spectrometer. As such a spectrometer, the MDU-Liulin equipment, developed in one of our laboratories was used. The equipment allows the data accumulated during the passage in or out of the South Atlantic Anomaly (SAA). In this paper, only the data obtained out of the SAA were analysed, assuming that the neutron spectra are similar to those onboard aircraft and/or at the CERF high-energy radiation field. The excess of deposited energy in the region above 1 MeV, when comparing with the aircraft field, was expected to represent the primary high-energy charged particles. Total dosimetry characteristics obtained in this way are in reasonable agreement with other data, neutron contribution representing approximately 40% of the total dose equivalent for the flight duration outside of the SAA.
Keywords: dávka záření; Equipment Failure Analysis; Occupational Exposure; Equipment Design; Neutrons; neutrony; Space Flight; pracovní expozice; kosmický let; reprodukovatelnost výsledků; design vybavení; kosmické záření; Reproducibility of Results; Cosmic Radiation; Radiation Dosage; Sensitivity and Specificity; senzitivita a specificita; radiační ochrana; Radiation Protection; monitorování radiace; analýza selhání vybavení; Radiation Monitoring